2013
DOI: 10.1108/ijcthr-02-2012-0006
|View full text |Cite
|
Sign up to set email alerts
|

Online reviews of short-term visits: exploring sense of place

Abstract: Purpose -This paper aims to explore the phenomenon of online vacation rentals (OVRs) (a new source of e-business travel growth) and how the concept of sense of place is presented by tourists' online reviews. Design/methodology/approach -The initial assumption for this exploratory study is that OVRs bring both material and intangible advantages to the individual consumer and to the community of homeowners. Using a qualitative approach, within the conceptual framework of a sense of place, multidimensional meanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This could occur when there are cognitive and affective stimuli in the form of physical buildings (architecture of the area), characteristics of the area, spatial interior, variety of products and a focal point as a landmark of the area (Kusumowidagdo et al , 2019). Dias et al (2013) demonstrated that a sense of place could be cultivated even before the tourists arrive, such as through online reviews of villas, which were the case of the study. The sense of place created were including the affordability of the destination, comfort and functionality.…”
Section: Literature Reviewmentioning
confidence: 87%
“…This could occur when there are cognitive and affective stimuli in the form of physical buildings (architecture of the area), characteristics of the area, spatial interior, variety of products and a focal point as a landmark of the area (Kusumowidagdo et al , 2019). Dias et al (2013) demonstrated that a sense of place could be cultivated even before the tourists arrive, such as through online reviews of villas, which were the case of the study. The sense of place created were including the affordability of the destination, comfort and functionality.…”
Section: Literature Reviewmentioning
confidence: 87%
“…Interpersonal influence and eWOM are classified as the most relevant information sources when consumers are in the decision-making process of making a purchase. This influence can be especially significant in the tourism and hospitality sector, as its intangible products are difficult to assess before consumption [41]. Collaborative and interactive platforms, e.g., 2.0 platforms, offer an accessible medium-where people can express their opinion and suggestions on any subject and where they can become co-creators-to create a space for co-creation between entities and audiences [42].…”
Section: User Generated Content (Ugc) and Electronic Word Of Mouth (Ewom)mentioning
confidence: 99%
“…The recent explosion in mobile information and communication technologies allows place and site visitors to share experiences and online text feedback or reviews over a more granular temporal and geographic scale that can inform SOP (23)(24)(25). An opportunity exists to examine SOP through the lens of data mining (i.e., extracting information and data online and forming digital narratives of place).…”
Section: Opportunities In Data Miningmentioning
confidence: 99%
“…Several applications of qualitative approaches exist, such as faceto-face interviews and case-specific interpretation by analysts. Dias et al analyzed online reviews of vacation rentals in Portugal through a qualitative approach and identified broad themes that described the surrounding landscape and leisure activities affiliated with a place and recommendations for rental owners and visitors (24). In another study, Oz and Temizel qualitatively analyzed reviews from Turkey on the website Foursquare to identify parts of speech indicating place attachment (26).…”
Section: Opportunities In Data Miningmentioning
confidence: 99%